Role of tonic GABAergic currents during pre- and early postnatal rodent development - Kilb, Werner; Kirischuk, Sergei; Luhmann, Heiko J. (Frontiers in Neural Circuits, 2013)
In the last three decades it became evident that the GABAergic system plays an essential role for the development of the central nervous system, by influencing the proliferation of neuronal precursors, neuronal migration and differentiation, as well as by controlling early activity patterns and thus formation of neuronal networks. GABA controls neuronal development via depolarizing membrane responses upon activation of ionotropic GABA receptors. However, many of these effects occur before the onset of synaptic GABAergic activity and thus require the presence of extrasynaptic tonic currents in neuronal precursors and immature neurons. This review summarizes our current knowledge about the role of tonic GABAergic currents during early brain development. In this review we compare the temporal sequence of the expression and functional relevance of different GABA receptor subunits, GABA synthesizing enzymes and GABA transporters. We also refer to other possible endogenous agonists of GABAA receptors. In addition, we describe functional consequences mediated by the GABAergic system during early developmental periods and discuss current models about the origin of extrasynaptic GABA and/or other endogenous GABAergic agonists during early developmental states. Finally, we present evidence that tonic GABAergic activity is also critically involved in the generation of physiological as well as pathophysiological activity patterns before and after the establishment of functional GABAergic synaptic connections.